2009
DOI: 10.1603/008.102.0508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performances of Wild Anastrepha obliqua (Diptera: Tephritidae) Individuals Proceeding From Different Hosts

Abstract: Feeding during the insect immature phase is extremely important for an adequate performance in adult life. The nutritional value of the ingested diet during the immature phase directly affects the percentage of emergence, the duration of the immature phase, and the size of the emerging adults. The objectives of this study were to compare the performance of adult Anastrepha obliqua (Macquart) (Diptera: Tephritidae) females, the pupae per kg of fruit, and the percentage of emergence of flies that spent the larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, we have to conclude that the vast bulk of individual size variation observed in this study is due to unknown endogenous and/or exogenous variables. While there is no doubt that size variation is important to individual fitness in tephritids, the growing body of field‐based literature (this study; Medeiros‐Santana & Zucoloto 2009; Navarro‐Campos et al . 2011; Bolzan et al .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, we have to conclude that the vast bulk of individual size variation observed in this study is due to unknown endogenous and/or exogenous variables. While there is no doubt that size variation is important to individual fitness in tephritids, the growing body of field‐based literature (this study; Medeiros‐Santana & Zucoloto 2009; Navarro‐Campos et al . 2011; Bolzan et al .…”
Section: Discussionmentioning
confidence: 71%
“…Given the numerous sources of variation in our data, we consider that detecting a positive protein‐size relationship must reflect a strong, underlying biological process for this species. In other fruit‐based studies, protein in the tephritid larval diet has not been identified as a nutrient of significance for pupal weight or wing length (Medeiros‐Santana & Zucoloto 2009; Hafsi et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation